Dem Menschen zugute. Götz Harbsmeier zum 60. Geburtstag - Prenter, Regin (Grundtvig-Studier, 1972)
Dem Menschen zugute. - Götz Harbsmeier zum 60. Geburtstag. Hrsg. Von K. E. Løgstrup und Emst Wolf. München 1970. Reviewed by Regin Prenter. On the back cover of the book under review it is claimed that the aim of all its contributors is to establish a positive relationship between Christianity and culture, but without indulging in a systematic Christian cultural synthesis. The reviewer asks the question whether all of them have actually succeeded. He finds that, in his settlement with the theology of Barth in a polemical epilogue, K. E. Løgstrup undisputably has succeeded. Løgstrup agrees with the Barthian theology that the Coming of God’s Kingdom is beyond philosophical cognition, and further, that the Coming of God’s Kingdom presupposes a common core of human experience. But he refuses to accept the point that this common core of human experience should be beyond philosophical cognition. Løgstrup also settles with the conception of this common core to be found in existential theology. It is true that Christ’s own preachings only mention such experience in passing. But this is due to the fact that what he said and did is the consummation of the Coming of God’s Kingdom. This cannot be said of the priest. He speaks of Jesu existence, which we (the priest) betray in our existence. What we say is not a message in itself, but only talk about a message; therefore we must “explain” . And therefore we cannot neglect the common core of human experience. In connection with Kaj Thaning’s interpretation of Grundtvig, Løgstrup emphasises Grundtvig’s repudiation of a Christian cultural synthesis. Although Christianity to Grundtvig was a message of the eternal salvation of the individual, this did not belittle the significance of earthly life. Christianity returns man to this life. Here man makes the experiences of life and death that make the message of an eternal life meaningful to him. It is suggested that in the last analysis Løgstrup agrees with Grundtvig rather than with Thaning. – In what follows the reviewer finds that Thaning’s contribution to the Festschrift is too orthodox in its Grundtvigianism - and this he regrets, for it makes dry reading. Apart from Løgstrup’s article the reviewer draws attention to Niels Thomsen’s article “That we should not despise Mystery and Cult” and Thorkild Bjørnvig’s “The young Dead - the young Living”. He also finds that Jørgen K. Bukdahl’s article on theological critique of Marxism is interesting reading matter. The crucial point is how we should understand man’s attidude to his own history. Is man created in the theological sense of the word, or is there nothing outside himself for him to take refuge to? - But how is the theologian to express his concept of creation in philosophical terms? Now and again Grundtvig is felt to be present in the background; but the book can by no means be regarded as presentation of Grundtvig as a challenge to the German philosophical and theological tradition, not even in Løgstrup’s and Thaning’s articles. This, however, is not a valid reason for not noticing the best of the contributions to the Festschrift. A summary of the last two reviews will appear in Grundtvig-Studier 1973.